Evidence of elevated levels of polychlorinated biphenyl congeners in commonly consumed fish from Eleyele Reservoir, Southwestern Nigeria (2016)
Environmental pollution of water, which is a source of cheap and affordable protein in the form of fish on which the population depends on, is of great concern globally. The present study assesses the levels of polychlorinated biphenyls (PCBs) congeners in sediments and six commonly consumed cichlid species from Eleyele Reservoir, Southwestern Nigeria. The results indicate that the concentrations of heavier PCB congeners are higher than the lighter congeners in both sediment and fish tissue. The predominant PCB congeners in the sediment samples from this site were PCBs 8, 44, 114, 101, 189, 196, 206 and 209. The concentration of PCB congeners increased with increasing molecular weight from hepta-PCB to deca-PCB in all fish species. The trend in accumulation of total PCBs in fish was as follows: Tilapia guineensis (2,531.1 + 74.6 ng/g) > Sarotherodon galilaeus (1178.7+68.5 ng/g) > Oreochromis niloticus > (891.8+49.6 ng/g) > Tilapia zillii (832.8 + 38.2 ng/g) > Hemichromis fasciatus (475.7 + 28.5 ng/g) > Sarotherodon melanotheron (333.2 + 26.1 ng/g). In summary, data from this study shows that the levels of PCBs in cichlid species from Eleyele Reservoir are higher than the threshold level of 0.023–0.047 ng g_1 recommended by United States Environmental Protection Agency. Such elevated PCB levels present significant health implications for human consumers and a threat to the resident fish communities.